Chemical Reduction of GO: Comparing Hydroiodic Acid and Sodium Borohydride Chemical Approaches by X-ray Photoelectron Spectroscopy - Wei Liu; Giorgio Speranza (C, 2022)
The efficiency of two wet chemical processes based on hydroiodic acid (HI) and sodium borohydride (NaBH4) used to reduce graphene oxide (GO) have been studied. At this aim, the oxygen abundance of reduced graphene oxide (rGO) was studied as a function of the reductant concentration. A number of rGO samples were produced and their chemical compositions were studied using X-ray photoelectron spectroscopy. The analyses show that the reduction of the oxygen concentration proceeds non-linearly. At the beginning, when pristine GO is utilized a higher extent of reduction is obtained. The oxygen concentration decreases from ~32% to 10.5% by increasing the HI concentration to 0.24 M. A steeper reduction was observed for NaBH4, where the oxygen concentration lowers to ~13.6% using just 50 mg of NaBH4. Next, reduction reactions performed with increasing amounts of reductants in aqueous suspensions show a progressive saturation effect, indicating a limit in the final oxygen concentration. We obtained a residual oxygen concentration of 5.3% using 7.58 M of HI and 8.6% with 1200 mg of NaBH4. The chemical analysis highlights that the reduction of the oxygen concentration in rGO samples is mainly derived from the cleavage of C-OH bonds and the next reconstruction of C-C bonds.